Emphasis and effectiveness of monetary policy of the Fed: a historical comparative analysis (1871-2013). (2017) - He, Ling T.
Results of this paper indicate that the effectiveness of monetary policy may reflect changes in policy emphasis on inflation and output growth. The evolution of the unmanaged to managed short-term interest rate as a monetary policy tool demonstrates a continuing correcting process of a biased sensitivity towards output growth in the gold standard era to a more balanced emphasis on price stability and output growth in the modern-Fed period. Evidence of this study suggests that the monetary policy with a more balanced emphasis on inflation and output can enhance the policy effectiveness measured by a simple assessment ratio which links GDP gap and standard deviation of inflation together so that the ratio can directly quantify the Fed's two top policy goals, promoting sustainable output growth and lowering price volatility.